Correlation analysis of serum PDK4, NLRP3, and PTEN levels in myocardial injury with sepsis: Serum PDK4, NLRP3, and PTEN levels in myocardial injury with sepsis - Fang, Zebin; Li, Xiaoxia; Ou, Zhenfei; Wang, Jimu; Lin, Keji; Ye, Shujia (Journal of Medical Biochemistry, 2025)
Objective: To explore the correlations between the levels of serum pyruvate dehydrogenase kinase 4 (PDK4), NOD-like receptor protein 3 (NLRP3), and phosphatase and tensin homolog (PTEN) deleted on chromosome 10 and myocardial injury indicators as well as prognosis in patients with sepsis. Methods: A total of 355 patients who were first diagnosed with sepsis and admitted to our hospital from September 2022 to September 2024 were included. Depending on whether they suffered myocardial damage, the patients were split into two groups: the septic myocardial injury (SIMI) group (225 patients) and the simple sepsis group (130 patients). According to their survival outcomes after 28 days of treatment, the patients were divided into two groups: the death group (56 patients) and the survival group (169 patients). The levels of serum PDK4, NLRP3 and PTEN were detected via real-time fluorescence quantitative PCR (qRT‒PCR). An automatic biochemical analyzer was used to measure the levels of myoglobin (Mb), cardiac troponin I (cTnI), creatine kinase isoenzyme (CK-MB), and heart-type fatty acid binding protein (H-FABP). The Pearson correlation coefficient method was used to analyze the relationships between serum PDK4, NLRP3, and PTEN levels and myocardial injury indicators in SIMI patients. Cox regression analysis was employed to examine the variables affecting SIMI patients’ prognoses. Results: The levels of serum PDK4, NLRP3, PTEN, CK-MB, cTnI, Mb and H-FABP in the SIMI group were significantly greater than those in the simple sepsis group (P<0.05). The levels of serum PDK4, NLRP3 and PTEN in patients with sepsis were positively correlated with the myocardial injury indicators CK-MB, cTnI, Mb and H-FABP (P<0.05). The APACHE II score, SOFA score, cTnI, and the levels of serum PDK4, NLRP3 and PTEN in the prognosis death group of SIMI patients were greater than those in the survival group (P<0.05). Independent risk variables that impact the prognosis of patients with SIMI include the APACHE II score, SOFA score, cTnI, PDK4, NLRP3, and PTEN (P<0.05). Conclusion: Serum PDK4, NLRP3 and PTEN, which are independent risk factors affecting the prognosis of SIMI patients, are highly expressed in SIMI patients.